Numerical simulation of Plateau's problem of minimal surfaces using nonvariational finite element method. Issue 5 (4th July 2016) - Mishra, Garima; Kumar, Manoj
Abstract : Purpose: – Numerical solution of Plateau's problem of minimal surface using non-variational finite element method. The paper aims to discuss this issue. Design/methodology/approach: – An efficient algorithm is proposed for the computation of minimal surfaces and numerical results are presented. Findings: – The solutions obtained here are examined for different cases of non-linearity and are found sufficiently accurate. Originality/value: – The manuscript provide the non-variational solution for Plateau's problem. Thus it has a good value in engineering application.